Energetic material characterization and ignition study of MEMS based micro-thruster for multi spacecrafts missions - Harshit Shukla; Gurunadh Velidi (FirePhysChem, 2024)
Over the past few years, there has been a growing recognition of the importance of multi-spacecraft missions for a variety of purposes, including Earth observation, navigation, guidance, climate monitoring, and environmental monitoring. The trend amongst agencies is to favour constellations of smaller satellites, which can aggregate data from various sources, rather than relying on larger satellites. The numerous benefits of multi-spacecraft formation flying missions have led to an increasingly growing interest to explore its propulsion technologies, i.e., micro propulsion. Thoroughly characterising and studying the behaviour of the energetic materials is essential to ensure the safe and effective use of these micro-thrusters. Through the optimisation of micro-thruster design, the current research aims to generate outcomes that can be utilised to enhance the design and optimisation processes. Consequently, this will facilitate the widespread utilisation of micro-thrusters in multi-spacecraft missions. To optimise the performance of pyrotechnic micro-electromechanical systems, an efficient heater design, appropriate base material, channel dimensions, and electrical resistance must be considered based on available power and heat transfer requirements. A unique firing and monitoring test setup has been developed to produce a current-time plot for the device. Additionally, different micro-heater configurations, including spiral, loop, and meander types, were designed for the igniter. Experimental observations indicate that the spiral micro-heater design resulted in the lowest ignition delay and produced highly reliable combustion. The proposed microthruster design demonstrated efficient combustion and yielded promising results when tested with energetic materials such as Zirconium Potassium Perchlorate (ZPP) and Boron Potassium Perchlorate (BPN).